4
$\begingroup$

Show that

$$I=\int_{0}^{1}(1-\sqrt[k]{x})^ndx={1\over {k+n\choose n}}$$

My try:

$x=u^k$ then $dx=ku^{k-1}du$

$$I=k\int_{0}^{1}(1-u)^n u^{k-1}du$$

$v=1-u$ then $dv=-du$

$$I=k\int_{0}^{1}v^n(1-v)^{k-1}dv$$

Using the binomial theorem to expand and integrate term by term is tedious, can anyone show me another quick easy way please? Thank you.

$\endgroup$
  • $\begingroup$ Your integral is a beta integral. Have you seen this notion ? $\endgroup$ – Jean Marie Dec 28 '16 at 22:44
  • $\begingroup$ That is interesting it changes into. Beta integral. $\endgroup$ – gymbvghjkgkjkhgfkl Dec 28 '16 at 22:49
7
$\begingroup$

Let $y=x^{1/k}$ \begin{align} \int\limits_{0}^{1} (1-x^{1/k})^{n} dx &= k\int\limits_{0}^{1} (1-y)^{n} y^{k-1} dy \\ &= k \mathrm{B}(k,n+1) \\ &= \frac{k\Gamma(k)\Gamma(n+1)}{\Gamma(k+n+1)} \\ &= \frac{k!n!}{(k+n)!} \\ &= {1\over {k+n\choose n}} \end{align}

We have used the beta and gamma functions.

$\endgroup$
3
$\begingroup$

By integration by parts, $$ B(a,b) = \int_{0}^{1}x^{a-1}(1-x)^{b-1}\,dx = \frac{\Gamma(a)\,\Gamma(b)}{\Gamma(a+b)}\tag{1} $$ so if $m$ and $n$ are natural numbers $$ \int_{0}^{1}x^m(1-x)^{n-1}\,dx = \frac{\Gamma(m+1)\Gamma(n)}{\Gamma(m+n+1)} = \frac{m!(n-1)!}{(m+n)!} = \frac{1}{n\binom{m+n}{n}}.\tag{2}$$ Have a look at Euler's Beta function.

$\endgroup$
1
$\begingroup$

Maybe you can try the Laplace transform. Let $f(t)=\int_0^t \tau^a(t-\tau)^b d\tau$, it's easy to compute $\mathcal{L}(f)(s)=\frac{a!b!}{s^{a+b+2}}$, then $f(t)=\frac{a!b!}{(a+b+1)!} t^{a+b+1}$.

$\endgroup$
1
$\begingroup$

First of all this is true for $n=1$.

Let's assume that it is true for $n=s-1$. Now we proceed to show that this is true for $n=s$.

Now $$I_s=\int_{0}^{1}(1-\sqrt[k]{x})^sdx=x(1-\sqrt[k]{x})^s|_0^1+\frac{s}{k}\int_0^1 x (1-\sqrt[k]{x})^{s-1} x^{\frac{1-k}{k} } dx=\frac{s}{k}\int_{0}^{1}x^{\frac{1}{k}}(1-\sqrt[k]x)^{s-1}=-\frac{s}{k}\int_{0}^{1}-x^{\frac{1}{k}}(1-\sqrt[k]x)^{s-1}=-\frac{s}{k}\int_{0}^{1}(1-x^{\frac{1}{k}})(1-\sqrt[k]x)^{s-1}+\frac{s}{k}I_{s-1}=-\frac{s}{k}I_s+\frac{s}{k}I_{s-1}$$ Then $$I_s \frac{s+k}{k}=\frac{s}{k}{1\over {k+s-1\choose s-1}}$$ Thus $$I_s=\frac{s}{s+k}\times \frac{(s-1)!k!}{(k+s-1)!}=\frac{s!k!}{(s+k)!}=\frac{1}{s+k \choose s}$$

Thus, This is true for all $n$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.